Scale-dependent dispersal drives community assembly of breeding birds along elevational gradients - Zhang, Kai; Wen, Zhixin; Wu, Yongjie; Yue, Yifan; Jia, Chenxi; Song, Gang; Lei, Fumin (Ecological processes, 2025)
Background Identifying the processes that govern community assembly along elevational gradients has been a central theme in ecology, especially in montane ecosystems where abundant species and strong turnover are present. However, our understanding of how the relative importance of deterministic and stochastic processes varies along elevational gradients remains limited. Here, we compiled a rigorously curated dataset of elevational distributions of 734 breeding bird species across the Hengduan Mountains in China to assess the dominant underlying mechanisms of bird community assembly at both intra-community and inter-community scales across four elevation zones: low, middle, subalpine, and alpine. Results At the intra-community scale, homogeneous dispersal played a pivotal role in driving community assembly of breeding birds across the Hengduan Mountains. Deterministic processes became more influential with increasing elevation, whereas stochastic processes prevailed in low, middle, and subalpine zones. At inter-community scale, assemblages from different elevation zones were more differentiated by dispersal limitation. Non-Passeriformes experienced more obvious influence of homogeneous dispersal but were less subject to dispersal limitation compared to Passeriformes. Conclusions Our findings highlight the role of stochastic processes in shaping biotic communities in montane ecosystems, but this effect is scale-dependent. The transition from stochastic to deterministic processes along elevational gradients suggests that environmental factors become more influential at higher elevations. Species dispersal ability may affect the relative importance of these two processes shaping community assembly.